Analysis of The Influence of Workload, Incentives, and Leadership Style on Employee Performance at the Class I Tpi Immigration Office Makassar - Indah Safriani Putri; Hasniaty; Nasir Hamzah (Yayasan Amerta Insan Unggul, 2025)
The purpose of this study is to examine the influence of workload, incentives, and leadership style, both partially and simultaneously, on improving employee performance at the Class I TPI Immigration Office Makassar. This research was conducted at the Class I TPI Immigration Office Makassar. Data were collected through observation, interviews, and documentation, and analyzed using quantitative descriptive analysis with multiple linear regression methods. Organizational management needs to formulate strategies for workload management, incentive provision, and the application of effective leadership styles. These strategies should include planning, implementation, and continuous policy control with the aim of achieving performance targets, maintaining a balance between productivity, job satisfaction, and employee loyalty, thereby enhancing the quality of public services provided by the Class I TPI Immigration Office Makassar. The findings of this study indicate that the three independent variables Workload (X₁), Incentives (X₂), and Leadership Style (X₃) have different effects on the dependent variable, Employee Performance (Y). Workload has a significant negative effect on employee performance, while incentives and leadership style have a significant positive effect. Incentives and leadership style contribute the most positively to employee performance, whereas excessive workload decreases performance.